The Great Waldo Pepper [videorecording (DVD)] - Redford, Robert; Svenson, Bo, 1944-; Sarandon, Susan, 1946-; Kidder, Margot; Goldman, William, 1931-2018; Hill, George Roy, 1921-2002 (GoodTimes Home Video, 1998)
A nostalgic tale of 1920s barnstorming pilots.